The overnight drift - Nina Boyarchenko; Lars C. Larsen; Paul Whelan (Federal Reserve Bank of New York, 2021)
We show that nearly 100 percent of the U.S. equity premium is earned over a window around the opening hours of European markets when U.S. cash markets are closed. We explore two potential complementary explanations. First, consistent with predictions from dealer inventory risk models, we find (1) a strong negative link to end-of-day order imbalance; (2) reversals are amplified in periods of high volatility; and (3) in recent years dealers have increasingly offloaded inventory during Asian trading hours. Second, shocks to end-of-day quantities of risk lead to increases in overnight expected returns.
Keywords: G13; G14; G15; 330; overnight returns; immediacy; inventory risk; volatility risk